The parainfluenza virus type 1 P/C gene uses a very efficient GUG codon to start its C' protein. - Boeck, R (1992)
Parainfluenza virus type 1 (PIV1) and Sendai virus (SEN) are very closely related, but the PIV1 P/C gene does not contain the ACG codon which initiates the SEN C' protein. Nevertheless, a protein corresponding to the PIV1 C' protein was observed both in vivo and in vitro. The initiation site of this protein maps upstream of the PIV1 C protein AUG in a region that does not contain an AUG codon. We have used site-directed mutagenesis to demonstrate that the PIV1 C' protein initiates from a GUG codon, four codons upstream of where the ACG is found in SEN. Remarkably, this GUG appears to initiate in vivo almost as frequently as AUG in the same context. However, whereas GUG permits downstream expression of the P and C proteins, AUG in this context does not. The conservation of an upstream non-AUG initiation codon for C' among PIV1 and SEN suggests that it is important for virus replication, even though some paramyxoviruses express only the C protein and others have no C open reading frame at all.